Segregación de funciones en la empresa “Eslo soluciones y más” de la ciudad de Ventanas, periodo 2022. - Contreras Jurado, Antonia Evelisa (2023)
This research was conducted at the company "Eslo soluciones y más", located in Los Ríos, Ventanas canton., which is dedicated to the sale of computers and peripheral equipment, software updates, technical service, corrective and preventive maintenance of desktop computers, laptops, printers, etc. The objective of this study was to analyze the organizational structure of the company, evaluating the internal functions, to determine the causes that affect the segregation processes, because it has problems in the segregation of personnel and lack of teamwork, do not have more staff at the place of service, lack of approval of purchase orders, delivery delays and customer service. The applied methodology is the analytical method that was used to determine behavior of the analyzed samples, evaluating the facts to find solutions and finding about the given problems with tools that are fundamental in this process, therefore the interview techniques and the evaluation of the factors of the internal ones were used, which allowed the obtaining of the following results: The functions within "Eslo soluciones y más", are a fundamental part, for the decrease of risks in every area that manages, by which for the fulfillment of these functions are taking a series of controls where the owner evaluates the different processes, on the other hand the performance of the organization by the employees is failing to comply with standards that make there are a variety of unplanned activities and that the company is only giving random activities and difficulties with greater importance are the shortage of staff in service and customer service, improve processes to help efficiently to what the customer wants to acquire.